Integrating Islamic Social and Commercial Finance in Financial Stability - Rahmat; Saparuddin Siregar; Marliyah; Ade Khadijatul Z. Hrp (Universitas Muhammadiyah Palu, 2023)
Integrating Islamic social and commercial finance into Islamic financial institutions can be important in maintaining the stability of the entire financial system by maximizing the role of zakat and waqf (as well as infaq, shadaqah) in the realization of micro and macro security. The aim of this research, which is a bibliographic study according to the opinions of Muslim economists, a study of the Islamic financial system and other research, reveals that documents used as discussions on the integration of Islamic economics, commercial finance and social are very important in efforts to improve the coherence of the financial system and social development. -economy in Indonesia. The type of data used by the author in this research is secondary data, namely data obtained from magazines, literary books and the Internet. The data obtained was then analyzed using descriptive analysis methods. From a macro perspective, sharia banking will increase financial system stability. If 0.5% waqf is applied to customer financing, then the waqf funds will accumulate every year. If 10% of savings customers become waqf each year, the waqf funds will accumulate for one year.